EFFECT OF INCLUSIVE LEADERSHIP (IL) ON INNOVATIVE WORK BEHAVIOR (IWB) OF SCHOOL TEACHERS: A PARALLEL MEDIATION ANALYSIS IN PLS – SEM (IITM Journal of Business Studies, 2025)
This study investigates the innovative work  behaviour of school teachers who practice in clusive leadership, with mediating roles of  workplace friendship and psychological safety.  Drawing on data from 308 school teachers,  PLS-SEM revealed that inclusive leadership  positively impacts innovative work behavior,  workplace friendship, and psychological safety.  Furthermore, both workplace friendship (WF)  and psychological safety (PS) significantly in fluence innovative work behavior and serve as  mediators in the relationship between IL and  IWL innovative work behavior. The results ac centuate the importance of fostering inclusive  leadership to enhance innovative work behav ior among educators, highlighting how work place friendships and psychological safety con tribute to creating an environment conducive  to innovation. The study provides practical im plications for educational institutions to prior itize inclusive leadership practices and cultivate  a supportive work atmosphere. By exploring  these dynamics, the research offers valuable in sights into strategies for enhancing innovation  in schools.
Keywords: investigates; environment; fosters